Optimising Bankruptcy Estate Recovery via Piercing the Corporate Veil: The Case of PT Sritex - Mulyono, Ferio Ivan (Media Iuris, 2025)
This study discusses the application of the Piercing the Corporate Veil (PCV) doctrine as an alternative to optimise the bankruptcy estate in the insolvency case of PT Sri Rejeki Isman Tbk (PT Sritex). PT Sritex was declared bankrupt by the Commercial Court of Semarang due to its failure to fulfil debt obligations amounting to IDR 29.8 trillion. The problem became more complex following the disclosure of alleged corruption by the former President Director, Iwan Setiawan Lukminto, who misused loan facilities totalling IDR 692.9 billion obtained from Bank BJB and Bank DKI. This case created an overlap between criminal asset confiscation and general bankruptcy execution, potentially reducing the value of the bankruptcy estate and harming creditors, particularly unsecured creditors. Therefore, the proposed solution is to optimise the bankruptcy estate by applying the PCV doctrine, which extends liability to the personal assets of directors, as stipulated in Law Number 40 of 2007 concerning Limited Liability Companies. This research employs a normative juridical approach, analysing statutory regulations, legal literature, and relevant court decisions. The findings indicate that the elements of Article 3 paragraph (2) and Article 104 paragraph (2) of the Company Law are fulfilled, directors can be held personally liable, and their assets drawn into the bankruptcy estate. To address the conflict between criminal and bankruptcy confiscation, a separation of assets is necessary, so that the proceeds of corruption can be returned to the state. In contrast, the legitimate assets of the company and its directors can still be distributed proportionally to creditors.